Causal Relationship between N-REIT's Dividend Yield and Money Market Indicators - Olusegun Olaopin Olanrele; Tomisi Olusegun Adegunle; Oluwatosin Babatola Fateye; Cyril Ayodele Ajayi; Rosli Said (Journal of African Real Estate Research, 2019)
This paper examined the relationship between the Nigerian Real Estate Investment Trusts (N-REITs) and Money Market Indicators (MMIs) which comprise of: Currency in Circulation (CIC), Broad Money Supply (BMS), Corporate-private Sector (CPS), Prime Lending Rate (PLR) and Treasury Bill Rate (TBR). Data for the N-REITs were sourced from the annual published report of SkyeREIT (an indirect real estate investment vehicle of Skye Shelter Fund Plc), while that of the MMI were sourced from the quarterly published bulletins of the Central Bank of Nigeria (CBN) and the National Bureau of Statistics (NBS) for the period 2008-2017. The study adopted the Co-integration test, Vector Autoregressive (VAR) and Vector Error Correction Model (VECM). The data collected passed the stationary test at p-value of p<0.05 which implies that the data is fit for Granger Causality Model (GSM) in a VAR environment. The co-integration test at 5% confidence level shows the existence of a partial long-run relationship at p-values of 0.0003, 0.0292 and 0.0297 respectively at the first three orders, while the Max-Eigen rank test was significant at the first order (none) with a p-value of 0.005. The results of the VAR and VEC models showed that CPS, PLR and TBR, with chi-square values of 11.748; 16.589; and 34.778 respectively, significantly affected the performance of N-REITs, while the PLR (4.5798) had a long-run significant effect. The findings provide decision caution for investors, analysts and capital market players when considering investment on securitised real estate assets.